A „Magyar Út” történetéről és szellemiségéről - András CSŰRÖS (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
The History and Ideology of the Periodical Magyar Út. The following study was originally presented at the 100th anniversary conference of the founding of Soli Deo Gloria. Magyar Út (Hungarian Way) is closely linked to Soli Deo Gloria Student Movement. It started from there and has remained its spiritual basis ever since. The paper describes the origins of the periodical, how it started, and how an organization’s newsletter became an independent weekly newspaper of great stature in just a few years. Beyond its history, the evolution of the ethos of the paper is also interesting. A further interesting aspect is that the journal was linked to the Magyar Testvériség (Hungarian Brotherhood) organization. The study provides an insight into the foreign policy ideas of the paper. The article concludes with a description of the journal’s life on the road – how they tried to continue in emigration and how the ideology that characterized Magyar Út lived on.